IMPLEMENTATION THE LAW OF REPETITION IN ACCOUNTING - Suharyono Suharyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
To prove that polytechnic graduates have qualified expertise in the field of accounting, then every student is required to follow the certification as a requirement of graduation. One of the competency units in the field of accounting that is regulated in the Indonesian National Competency Standards is to operate computer accounting applications. The purpose of this study was to find out the comparison of computer-based accounting certification passing grade level between before and after implementation of law of repetition. Participants who joined law of repetition activities amounted to 52 people. The results showed that the number of students who passed computer-based accounting certification after Participants who joined law of repetition activities amounted to 52 people was 24 people. These results increased 100% when compared before the implementation law of repetition. The independent sample t test showed a significance of 0%. The significance is smaller than p value of 5%, hence this means computer-based accounting certification pass rate after law of repetition has a significant difference when compared to computer-based accounting student certification graduation rate before law of repetition. The results of this study prove that law of repetition has an important role in helping prepare students in facing computer-based accounting certification test.